Conditioning of Temperature and Soil Moisture in Chrysanthemum Cut Flowers Greenhouse Prototype based on Internet of Things (IoT) - Fauziyah, Mila; Safitri, Hari Kurnia; Dewatama, Denda; Aulianta, Erdin (ELKHA : Jurnal Teknik Elektro, 2021)
Currently, cut chrysanthemum cultivation in a greenhouse is still using a conventional system. Temperature and soil moisture are the most important factors in the growth process. If the temperature and humidity of the soil are not conditioned, the roots will quickly rot and slow the growth process of chrysanthemums. Internet of Things is an integrated system with a data-based server that stores data in the cloud from sensors so that the system can be monitored remotely in real-time. Based on this, an integrated system was designed to make it easier for farmers to condition the temperature and humidity of the chrysanthemum flower soil. In temperature conditioning, if the temperature of cut chrysanthemum is detected 24 â„ƒ then the heater will be "on" by adjusting the fan rotation and vice versa. Meanwhile, soil moisture conditioning is carried out by distributing water if the detected soil moisture is 50%, then the water pump is in the "on" state. The data on the degree of temperature and the percent of soil moisture will be recorded into the cloud which will then be displayed in the form of graphs and history data on the webserver and Android. By using this system, it is found that the growth process of cut chrysanthemums can grow 7 days faster than the standard harvest time of 30 days.